Implementation of Fuzzy Logic to Control Temperature and Incubation Time for the pH of Yoghurt - ratna aryanti; Chika Hayya Sabillah; Muhammad Faiz Assariy; Daffa Zulqihisti; Ronnauli Lamria Sirait; Rizki Laksana Putra; Maharshi Kaloka Parahita; Fauzan Maula Abdullah; Dhiya Ananta Pranadita; Delia Noor S; Afrida Rif'atul Hanifa; Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
This research develops a fuzzy logic-based yoghurt production model by considering incubation temperature and incubation time as the main variables that influence the final pH of yoghurt. In this study, 49 yoghurt samples were produced and tested in two replications to obtain pH data which was then processed through fuzzy modeling. This fuzzy model is for determining fuzzy rules and membership functions. By using two fuzzy sets for each parameter and the Mamdani method, a total of 49 fuzzy logic rules were built to describe the relationship between incubation variables and final pH. Matlab 2015a software was used to process data and assess model accuracy. The results showed that this model was effective for predicting the final pH of yoghurt, which is important for maintaining product quality. In the future, it is hoped that this model can be applied to automated production lines, thereby supporting yoghurt production on an industrial scale with greater consistency and efficiency, especially ini the food sector.